Proceedings of the Eighth International Workshop on Object-Oriented Real-Time Dependable Systems, 2003. (WORDS 2003).
DOI: 10.1109/words.2003.1218075
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Web services using an enhanced UDDI server

Abstract: The UDDI (Universal Description Discovery and Integration) provides classification to find the distributed Web Services (WS) by keyword matching. The UDDI version 3 allows searching WS using digital signatures. However, it still needs systematic verification to ensure WS quality in a timely fashion. This paper proposes adding verification mechanism to the UDDI servers including check-in and checkout of WS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 5 publications
0
38
0
1
Order By: Relevance
“…EB is trusted by both c and sp to correctly check the certificate validity on the basis of the monitoring rules and metrics. v) Service Discovery (UDDI), a registry of services (e.g., [26]) enhanced with the support for reliability certificates and requirements.…”
Section: An Architecture For Reliability Certificates Checkingmentioning
confidence: 99%
“…EB is trusted by both c and sp to correctly check the certificate validity on the basis of the monitoring rules and metrics. v) Service Discovery (UDDI), a registry of services (e.g., [26]) enhanced with the support for reliability certificates and requirements.…”
Section: An Architecture For Reliability Certificates Checkingmentioning
confidence: 99%
“…The possibility of enhancing the functionality of a UDDI service broker with logic that permits to perform a testing step before registering a service has been firstly proposed in [28] and [27], and subsequently in [20]. This idea is also the basis for the framework introduced in this paper.…”
Section: Related Work In Testing Of Web Servicesmentioning
confidence: 99%
“…With reference to the information that must be provided with the WS description, the authors of [28] foresee that the WS developer provides precise test suites that can be run by the enhanced UDDI. In [20] instead the authors propose to include Graph Transformation Rules that will enable the automatic derivation of meaningful test cases that can be used to assess the behavior of the WS when running in the "real world".…”
Section: Related Work In Testing Of Web Servicesmentioning
confidence: 99%
“…Some similar broker based architectures were presented in [12] and [13] that focus more on the QoS specification using XML schema, and dynamic QoS mapping between server and network performance. In [14], Tsai et al suggested test scripts specification techniques to perform testing with the UDDI server. The verification tests are performed in UDDI registry that does not support QoS-aware web service publication and discovery.…”
Section: Background and Related Workmentioning
confidence: 99%